Nocardia spp. Pneumonia in a Solid Organ Recipient: Role of Linezolid - George Mwandia; Hari Polenakovik (Case Reports in Infectious Diseases)
We describe a rare infection with Nocardia spp. (N. pseudobrasiliensis species identification based on high-performance liquid chromatography analysis) in a 68-year-old renal transplant recipient. He presented with pneumonia complicated by hypoxic respiratory failure. He was allergic to sulphonamides. He was initially successfully treated with linezolid. However, he suffered severe sensory neuropathy after 4 months of therapy, necessitating linezolid cessation and completion of treatment with azithromycin. He had clinical and radiological resolution of his pneumonia and was disease free at subsequent follow-up 4 years later. This case highlights the need for alternative therapies for nocardiosis for patients that cannot be treated with sulphonamides due to allergies or/and infection with multidrug-resistant pathogens. It also illustrates the treatment limiting side effects of long-term therapy with linezolid.